The aging signature: a hallmark of induced pluripotent stem cells? - Rohani, Leili; Johnson, Adiv A.; Arnold, Antje; Stolzing, Alexandra (Aging cell, 2014)
Summary The discovery that somatic cells can be induced into a pluripotent state by the expression of reprogramming factors has enormous potential for therapeutics and human disease modeling. With regard to aging and rejuvenation, the reprogramming process resets an aged, somatic cell to a more youthful state, elongating telomeres, rearranging the mitochondrial network, reducing oxidative stress, restoring pluripotency, and making numerous other alterations. The extent to which induced pluripotent stem cell (iPSC)s mime embryonic stem cells is controversial, however, as iPSCs have been shown to harbor an epigenetic memory characteristic of their tissue of origin which may impact their differentiation potential. Furthermore, there are contentious data regarding the extent to which telomeres are elongated, telomerase activity is reconstituted, and mitochondria are reorganized in iPSCs. Although several groups have reported that reprogramming efficiency declines with age and is inhibited by genes upregulated with age, others have successfully generated iPSCs from senescent and centenarian cells. Mixed findings have also been published regarding whether somatic cells generated from iPSCs are subject to premature senescence. Defects such as these would hinder the clinical application of iPSCs, and as such, more comprehensive testing of iPSCs and their potential aging signature should be conducted.